Encyclopedia of case study research - Durepos, Gabrielle; Mills, Albert J. , 1945-; Wiebe, Elden (SAGE, 2010)
Intended to be the authorative reference work, this interdisciplinary set takes a look at the extensive history, design and methods of case study research.